A phase 1/2a dose-finding study and biomarker assessment of oral lisavanbulin in patients with high-grade glioma or glioblastoma - Lopez, Juanita Suzanne; Haefliger, Simon; Plummer, Ruth; Clement, Paul M.; Jeffry Evans, Thomas R.; Läubli, Heinz; Roth, Patrick; Kristeleit, Rebecca; Brazil, Lucy; Tabatabai, Ghazaleh; Wick, Antje; Wunderlich, Benjamin; et al. (Cell reports. Medicine, 2025)
Lisavanbulin is a prodrug of the microtubule-targeting agent avanbulin. Both avanbulin and lisavanbulin have demonstrated significant antitumor activity in several preclinical tumor models including glioblastoma. Previous human studies demonstrated that 48-h infusions of intravenous lisavanbulin were well tolerated with preliminary activity in recurrent glioblastoma. The current phase 1/2a study evaluates the safety and tolerability of once-daily oral lisavanbulin in patients with solid tumors or recurrent glioblastoma or high-grade glioma. Lisavanbulin is associated with profound, durable responses in a subset of patients with recurrent refractory grade 4 astrocytoma or glioblastoma. We present here the clinical and translational results from this trial, including a description of a response-predictive molecular signature that warrants further exploration in these tumor types of significant unmet need. The study is registered at ClinicalTrials.gov (NCT02490800). [Display omitted] •Lisavanbulin is an orally dosed brain-penetrant mitotic spindle checkpoint inhibitor•Our study assesses lisavanbulin in refractory astrocytoma or glioblastoma•Lisavanbulin is tolerable in patients with these tumors•A subset of patients have durable efficacy responses to lisavanbulin Lopez et al. report a phase 1/2a study evaluating once-daily oral lisavanbulin, a brain-penetrant microtubule-targeting agent in patients with solid tumors or recurrent high-grade glioma. Lisavanbulin is tolerable in these patients and is associated with profound, durable responses in a subset of patients with grade 4 astrocytoma or glioblastoma.